Diagnosis of Streptococcus pneumoniae infection using circulating antibody secreting cells - Shuya Kyu (Public Library of Science (PLoS), 2021)
Background Streptococcus pneumoniae infections cause morbidity and mortality worldwide. A rapid, simple diagnostic method could reduce the time needed to introduce definitive therapy potentially improving patient outcomes. Methods We introduce two new methods for diagnosing S. pneumoniae infections by measuring the presence of newly activated, pathogen-specific, circulating Antibody Secreting Cells (ASC). First, ASC were detected by ELISpot assays that measure cells secreting antibodies specific for signature antigens. Second, the antibodies secreted by isolated ASC were collected in vitro in a novel matrix, MENSA (media enriched with newly synthesized antibodies) and antibodies against S. pneumoniae antigens were measured using Luminex immunoassays. Each assay was evaluated using blood from S. pneumoniae and non-S. pneumoniae-infected adult patients. Results We enrolled 23 patients with culture-confirmed S. pneumoniae infections and 24 controls consisting of 12 non-S. pneumoniae infections, 10 healthy donors and two colonized with S. pneumoniae. By ELISpot assays, twenty-one of 23 infected patients were positive, and all 24 controls were negative. Using MENSA samples, four of five S. pneumoniae-infected patients were positive by Luminex immunoassays while all five non-S. pneumoniae-infected patients were negative. Conclusion Specific antibodies produced by activated ASC may provide a simple diagnostic for ongoing S. pneumoniae infections. This method has the potential to diagnose acute bacterial infections.